The omnivore's dilemma : a natural history of four meals - Pollan, Michael, 1955- (Penguin, 2007)
Today, buffeted by one food fad after another, America is suffering from what can only be described as a national eating disorder. Will it be fast food tonight, or something organic? Or perhaps something we grew ourselves? The question of what to have for dinner has confronted us since man discovered fire. But as Michael Pollan explains in this revolutionary book, how we answer it now, at the dawn of the twenty-first century may determine our survival as a species.--From publisher description.